Quicksand - Persson Giolito, Malin, 1969- (Other Press, 2017)
"QUICKSAND is an incisive courtroom thriller and a drama that raises questions about the nature of love, the disastrous side effects of guilt, and the function of justice. A mass shooting has taken place at a prep school in Stockholm's wealthiest suburb. Maja Norberg is eighteen years old and on trial for her involvement in the massacre where her boyfriend and best friend were killed. When the novel opens, Maja has spent nine excruciating months in jail awaiting trial. Now the time has come for her to enter the courtroom. But how did Maja, the good girl next door who was popular and excelled at school, become the most hated teenager in the country? What did Maja do? Or is it what she didn't do that brought her here?"--